Kesulitan Mahasiswa dalam Memecahkan Masalah Statistika Dasar - Fetti Fatricia Amdar; Jemmy Eko S.Putra; Almi Khaerah; Irmayanti (Yayasan Pendidikan Internasional Bengkulu, 2023)
The purpose of this study was to determine students' difficulties in solving mathematical problems in Basic Statistics courses. The research method used to achieve the objectives of this research is qualitative research, with a research focus on identifying students' difficulties in solving mathematical problems. This research involved 6 3rd semester students who contracted the Basic Statistics course in the Mathematics Tadris Study Program at the Muhammadiyah Islamic Institute of Religion (IAIM) Sinjai Academic Year 2022/2023. The ability to solve problems in this study uses the indicators proposed by Polya, namely (1) understanding the problem (2) planning a solving strategy, (3) solving problems and (4) re-examining the results of the solution. The results of the investigation show that: (1) students have difficulty understanding problems such as students cannot understand what is known and asked in problems, students have difficulty understanding information presented in the form of diagrams, (2) students have difficulty choosing problem-solving strategies. Student difficulties at this problem-solving stage result in students not being able to proceed to a higher problem-solving stage.